Determination of progesterone (P4) from bovine serum samples using a microfluidic immunosensor system - Arevalo, Fernando Javier (2010)
Progesterone (P4) is a steroidal hormone with a vital role in the maintenance of human and animal health. This paper describes the development of an immunosensor coupled to glassy carbon (GC) electrode and integrated to a microfluidic system to quantify P4 from bovine serum samples in a fast and sensitive way. The serum samples spiked with a given P4 concentration and a given P4 concentration bound to horseradish peroxide (HPR) were simultaneously added and, therefore, they competed immunologically with sheep monoclonal anti-P4 antibodies that were immobilized at a rotating disk. HRP in the presence of hydrogen peroxide (H2O2) catalyzes the chatecol (H2Q) oxidation to benzoquinone (Q). Its reverse electrochemical reduction to H2Q can be detected at a GC electrode surface at -0.15 V by chronoamperometric measurements. These current responses are proportional to the enzyme activity and inversely proportional to the P4 amount present in bovine serum samples. This P4 immunosensor showed a linear working range from 0.5 to 12.5 ng mL-1. The detection (DL) and quantification (QL) limits were 0.2 and 0.5 ng mL-1, respectively. The electrochemical immunosensor had a higher sensitivity than the ELISA method using conventional spectrophotometric detections. However, both methods allowed us to obtain similar detection limits. The immunosensor allowed us to make up to 100 determinations on different samples without any previous pre-treatment. This behavior proved to be suitable to detect P4 in routine veterinary, clinical, biological, physiological, and analytical assays.